De la musique à l’argument - Pénélope Daignault; Audrey Dupuis; Maxime Boivin; Mikaël Guillemette (Communication)
The authors look at 71 audiovisual election ads produced by the two main political parties in Quebec during the last two provincial elections, in 2012 and 2014. Their analysis seeks to characterize the tone of the ads on a positive/negative continuum by taking into account various audiovisual elements and the types of argument they employ. The results offer no evidence that negativity was dominant. On the contrary, most elements analyzed were used in a positive way to highlight the qualities of a party, its leader, or its candidates.